Reviewing Morphologic Specifications of Acorn Leaves and Fruits in Lorestan Province - Nazar , Naser; Delfan, Saeedeh; Zand, Farhad (Asian Journal of Agriculture and Rural Development, 2015)
Zagros forests, as the greatest jungle area of the country, are considered not only as a high-economic zone in wooden products, but also as a highly important zone in environmental values. It should be mentioned that acorn is one of the main elements in the forests of Lorestan, and grows on different ecologic conditions’ realizing the variance-range of quantities and qualities aspects of leaves and fruits. This research has been done within the seven zones of Lorestan province’s acorn forests. 40 samples of leaf and fruit have been gathered from various trees. For each sample, 8 morphological aspects of fruit, and 16 morphological aspect of leaf were measured and recorded. Received data were statistically analyzed by Minitab ver.14 software. Results show that there are three types of acorn in the province of Lorestan: Quercus Persica (Persian acorn), Quercus Branti (Broodar), and Quercus Infectoria (Darmazoo). The quercus infectoria can be seen separately on the zone of Zasht & Ghalai; two types of branti and persica can be seen irregularly. On Ghalai zone, due to the rain fall rate and more humidity in comparison to other zones, suitable conditions are available for the growth of Quercus infectoria. Among the reviewed aspects in this research, leaf color, the existence of fluff on leaves, existence of teeth, and the length of grain cover have the greatest effect on the separation of Persia and branti from infectoria.